Demographic and socioeconomic changes in Sabah - Tey, Nai Peng (Penerbit UMS, 2021)
Population and development are inextricably interrelated. Population size and structure are crucial factors affecting opportunities, pressures, and constraints of society. The high fertility and rapid population growth in low-resource countries have hampered socio-economic development. However, as fertility began to fall rapidly since the middle of the 20th century, many postdemographic-transition countries are undergoing rapid population ageing and encountering labour shortages. Sabah is the second-most populous state in Malaysia, with about 4 million population in 2020. It has registered the secondhighest population growth rate over the past four decades, brought about by the influx of migrant workers due to the severe labour shortage. T.ne numbe½ of non-citizens grew from 20 thousand in 1990 to 1.094 million in 2020. Non-citizens made up close to 30% of the state population during 2013 - 2018, up from around 26% in 2009- 2010. However, the negative growth of the non·citizens in Sabah during 2018- 2020 has resulted in zero growth of the state population.